Analysis Content Marketing On Purchase Intention Through Customer Engagement (Study on @sakinahkonveksi_1803) - Angga Maulana; Kokom Komariah; Sopyan Saori (LP2M IAIN Palopo, 2025)
This research aims to examine the influence of Content Marketing on Purchase Intention, with Customer Engagement serving as a mediating variable. In the context of consumer purchase Intention, awareness of content marketing strategies—particularly those emphasizing sustainability—is becoming increasingly essential. The research employed a survey method by distributing questionnaires to 300 followers of the Instagram account @sakinahkonveksi_1803. The collected data were then analyzed using path analysis to assess the relationships among the variables studied. The findings reveal that Content Marketing exerts a positive and significant impact on Customer Engagement, and in turn, Customer Engagement positively influences Purchase Intention. Furthermore, Customer Engagement is confirmed to act as a mediating variable that reinforces the relationship between Content Marketing and Purchase Intention. These results suggest that well-implemented Content Marketing strategies can boost Customer Engagement, which subsequently enhances consumers' intentions to purchase. This study offers valuable insights for businesses in formulating more effective marketing strategies.